1994
DOI: 10.1111/j.1549-0831.1994.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Attachment and Depression Among Residents in Two Rural Midwestern Communities1

Abstract: ABSfRAGr The relationship between community attachment and depression is examined in a sample survey (N = 295) in two midwestern rural towns and their surrounding open-country areas. When community attachment, a variable through which a rural resident's social integration into the local community affects mental health, was low, higher levels of symptoms of depression were observed. The economic viability of the local community was found to have a relationship to mean depression scores in the towns but not in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Published as Alcock, I., White, M.P., Lovell, R., Higgins, S.L., Osborne, N. They may also differ in factors which are not controlled in the models. A potentially relevant factor is residential area attachment, which is related to mental health (Pevalin, 2003;O'Brien et al, 1994), and may also be related to land cover. It may be, for instance, that neighbourhood attachment was lower amongst those who re-located and, precisely because of this, it was these individuals who sought to move to an area they would like more and which would make them happier.…”
Section: Links To Other Researchmentioning
confidence: 99%
“…Published as Alcock, I., White, M.P., Lovell, R., Higgins, S.L., Osborne, N. They may also differ in factors which are not controlled in the models. A potentially relevant factor is residential area attachment, which is related to mental health (Pevalin, 2003;O'Brien et al, 1994), and may also be related to land cover. It may be, for instance, that neighbourhood attachment was lower amongst those who re-located and, precisely because of this, it was these individuals who sought to move to an area they would like more and which would make them happier.…”
Section: Links To Other Researchmentioning
confidence: 99%
“…Several studies have found associations between community cohesion and mental health difficulties (Aneshensel & Sucoff, 1996;O'Brien, Hassinger, & Dershem, 1994). However, the mechanism through which these community variables may buffer individuals against negative psychological outcomes has rarely been explored.…”
Section: Abstract Anxiety Terrorism Community Cohesion Israelmentioning
confidence: 96%
“…This evidence has instigated a new wave of research stemming from different disciplines such as rural sociology, cultural anthropology, social geography, community and applied social psychology. A rapidly expanding multi-disciplinary research field called 'rural mental health' has dynamically emerged exploring psychological effects of rural transformations on both farmers' lives and entire rural communities (O'Brien, Edward, & Dershem, 1994). Apart from examining the prevalence and incidence of psychological problems among farmers, a research concern has been to identify aspects of rural communities that can buffer against farmers' hardships acting as community resources (Wainer & Chesters, 2000).…”
Section: Introductionmentioning
confidence: 99%